Current approaches to the diagnosis and treatment of white sponge nevus. (29th May 2015) - Cai, Wenping; Jiang, Beizhan; Yu, Fang; Yang, Jianhua; Chen, Zhenghu; Liu, Junjun; Wei, Rongbin; Zhao, Shouliang; Wang, Xiaoping; Liu, Shangfeng
Abstract : White sponge nevus (WSN) in the oral mucosa is a rare autosomal dominant genetic disease. The involved mucosa is white or greyish, thickened, folded and spongy. The genes associated with WSN include mutant cytokeratin keratin 4 ( KRT 4) and keratin 13 ( KRT 13). In recent years, new cases of WSN and associated mutations have been reported. Here, we summarise the recent progress in our understanding of WSN, including clinical reports, genetics, animal models, treatment, pathogenic mechanisms and future directions. Gene-based diagnosis and gene therapy for WSN may become available in the near future and could provide a reference and instruction for treating other KRT-associated diseases.